GYMNASTIC TRAINING IN THERAPY HORSES IMPROVES QUALITY OF THE TRIDIMENSIONAL MOVEMENT OF TROT - Oliveira, K.; Bocci, C. L.; Patini, A. F.; Araújo, M. S. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The objective of this study was to determine if therapy horses submitted to gymnastic training developed a better quality of three-dimensional movement of trot, evaluated by means of biomechanical variables as cadence, regularity and symmetry. Twenty therapy horses were used with a mean age of 19 ± 3.5 years and mean live weight of 440 ± 50 kg. The treatments consisted of a total of five experimental groups, consisting of a control group (without exercise) and four test groups of horses submitted to gymnastic training, with weekly frequencies increasing, ranging from one to four times a week. Gymnastic training was performed during a three-month period. The design was completely randomized, resulting in four replications per treatment. The biomechanical variables related to the coordination of the gait were analyzed, such as, cadence of the stride (CAD), regularity of the stride (REG) and symmetry of the stride (SYM), to determine the quality of the three-dimensional movement, using the Equimetrix accelerometer. There was no significant effect for trotting CAD gain (P> 0.05). However, an improvement in the gains of REG and SYM was observed (P <0.05), in which the best results were found in horses submitted to gymnastic training performed three to four times a week, with values of 15.4 and 16.0 (/ 200) for REG and of 14.9 and 20.6 (%) for SYM, respectively. It was concluded that the performance of gymnastic training in therapy horses, from three sessions per week, improves the three-dimensional movement of the trot, due to the gain in regularity and symmetry, with the same cadence of the stride.